Which Assessment of Coach-Created Motivational Climate Better Predicts Young Athletes’ Engagement over a Season? Athletes’ Perceptions and Match Observations Do - Raimundi, María Julia (2023)
This work examines athletes’ and coaches’ perceptions and observed behavior in training and matches of the motivational climate created by the coach over the course of a season and whether these sources of information can inform the engagement of young basketball and volleyball players. A longitudinal design and multilevel mixed-effects linear regression models were conducted. Adolescents (n = 517) of both genders (61.1% male, 38.9% female) aged between 12 and 20 years (M = 16.01; SD = 1.85) playing in the A division of the basketball (46.4%) and volleyball (53.6%) federation of Buenos Aires (Argentina) participated in the study. In addition, 48 coaches (83% male, 17% female; M age = 33.98; SD = 8.39) from these teams participated. The coaches were videotaped during the training sessions in the three waves of measurements. Observers used the Multidimensional Motivational Climate Observational System. Athletes and coaches completed a socio-demographic questionnaire, and the Empowering and Disempowering Motivational Climate Questionnaire-Coach. Athletes also completed the Athlete Engagement Questionnaire. Differences were found between perspectives and, in general, a decrease in variables characterizing empowering climates and an increase in those characterizing disempowering climates were observed over the course of the season. When all measures are considered together and the effect of time is controlled for, the assessments that predict engagement are athlete perceptions and match observations.